Case Report: Delayed recurrence of staphylococcal scalded skin syndrome in an extremely low birth weight infant - Hooper, Sara M.; Fung, Camille M.; Torr, Carrie; Lawrence, Shelley M. (Frontiers in Pediatrics, 2025)
Preterm infants have well-documented deficiencies in their innate and adaptive immune responses, which are indirectly correlated with their gestational age at birth. They also exhibit low levels of circulating immunoglobulins due to the lack of maternal transplacental IgG transfer during the third trimester of pregnancy. These factors place them at a particularly high risk for infectious diseases after birth. Diagnosing infections that primarily manifest through abnormal skin findings can be challenging, given overlapping characteristics attributed to bacterial and yeast pathogens. The case presented involves an infant born extremely premature with staphylococcal scalded skin syndrome (SSSS), a diagnosis rarely made in neonatal patients. However, he was initially treated for a yeast infection of his neck and skin folds, which is very common. This patient's course was complicated by a family history concerning for an undiagnosed, inherited immune deficiency. This case highlights the clinical findings and management of SSSS in preterm infants. It also details the importance of establishing a specialized multidisciplinary team to coordinate and manage the care of these patients.